Government provision and regulation of bus service in Cairo - Elkaramany, Mohamed Abdelsalam (AUC Knowledge Fountain, 2015)
The Cairo Transport Authority (CTA), an economic agency affiliated to Cairo Governorate, is responsible for operating the publicly owned buses, in addition to its role as the market regulator of transit bus. The bus service provided by the CTA covers Greater Cairo region, an extensive geographical area including three Governorates; Cairo, Giza and Qalyubia. Given the wide spread of poverty in Greater Cairo, the necessity to commute and the positive externalities associated with people’s mobility, the Government of Egypt controls the bus fares to make public bus ridership affordable to a broad range of clientele. Accordingly, it supports the CTA through a generous subsidy package that kept growing over the years. Even though, the CTA suffers from the inherited problems of the bureaucracy such as the overstaffing and the chronic budget deficits. Such being the case, it was essential to assess how the government intervention through service provision and regulation affects the quality of bus service. Since the available data is not sufficient to conduct quantitative analysis which is more frequently used in transport economics, a qualitative approach was pursued to investigate whether the CTA is capable of providing a convenient bus service. Based on the findings of a focus group discussion and in depth interviews with commuters, the term convenience encompasses travel time, service reliability, accessibility and comfort. The findings suggested that the travel time is high, the service is neither reliable nor comfortable and also there are some problems regarding operating times and facilities for people with disabilities.